Hadith #4947 - Sunan Abi Dawud - Aabad bin 'Aabad bin Habib عباد بن عباد بن حبيب بن المهلب; ibn Umar; Ibrahim bin Ziyad al-Bghdady إبراهيم بن زياد البغدادي; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
Your prophet (May peace be upon him) said : Every good act is a SADAQAH (almsgiving).
Grade: Sahih